Comparison of Demographic Parameters and Predation Rates of Orius strigicollis (Hemiptera: Anthocoridae) Fed on Eggs of Tetranychus urticae (Acari: Tetranychidae) and Cadra cautella (Lepidoptera: Pyralidae) - Tuan, Shu-Jen; Yang, Chung-Ming; Chung, Yi-Ting; Lai, Wei-Han; Ding, Han-Yan; Saska, Pavel; Peng, Shu-Chen (Journal of economic entomology, 2016)
Orius strigicollis (Poppius) is an anthocorid bug with high foraging ability on thrips as well as on mites, and the bug has been considered as a potential biological control agent in Taiwan. Life table and predation studies of O. strigicollis fed on Cadra cautella (Walker) and Tetranychus urticae (Koch) eggs were conducted at 25 ± 1°C. Data were analyzed and compared using TWOSEX-MSChart and CONSUME-MSChart software. O. strigicollis fed on eggs of C. cautella, a substitute prey, showed significantly higher survival rate and developmental rate than individuals fed on their natural prey, T. urticae eggs. The fecundity of O. strigicollis fed on C. cautella eggs was, on average, 13.2 times higher than that of those fed on T. urticae eggs, despite of the fact that during the entire nymphal stage, the consumption rate of O. strigicollis on T. urticae eggs was ca. 9 times higher than on almond moth eggs The conversion rate (i.e., number of prey eggs needed to produce one predator egg) for this predatory bug reared on T. urticae eggs and almond moth eggs were 604.6 and 6.0, respectively, indicating that almond moth eggs served as an effective alternative prey for ensuring the predator's reproduction. This is the first study pertaining to the population parameters and predation rates of O. strigicollis using the age-stage two-sex approach to describe differences between O. strigicollis populations reared on natural and alternative preys. This information may be useful in mass rearing programs and field application involving this biological control agent.
Keywords: Ovum; Heteroptera; biologická kontrola škůdců; ovum; Nymph; zvířata; Predatory Behavior; nymfa; mužské pohlaví; Diet; Tetranychidae; Moths; ženské pohlaví; predátorské chování; tabulky života; Pest Control, Biological; Animals; Life Tables; dieta; můry; Male; Female